2004
DOI: 10.1159/000076918
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Feeding Formula and Breast Milk Fortifier on Lymphocyte Subsets in Very Low Birth Weight Premature Newborns

Abstract: Background: It is well known that breast-feeding protects the newborn from infectious diseases. This is especially important for very low birth weight preterm infants, whose immune systems are immature. In this study we investigated how a milk fortifier and replacement formula affected lymphocyte subsets in preterm infants. Method: The study assessed the effects of different types of feeding (human milk, n = 14; fortified human milk, n = 16; formula, n = 14) on lymphocyte subsets in 44 very low birth weight pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…34 In a small study of preterm infants, infants fed breast milk also had lower B-cell counts than infants who were fed formula. 35 Because of the immaturity of the neonatal humoral response, infants facing infection rely on maternal antibodies and a robust cytotoxic Th1 response. Enhanced cytotoxic function in infants fed breast milk may be promoted by bacterial ligands in breast milk.…”
Section: Proposed Function Of Microbiota In Human Breast Milkmentioning
confidence: 99%
“…34 In a small study of preterm infants, infants fed breast milk also had lower B-cell counts than infants who were fed formula. 35 Because of the immaturity of the neonatal humoral response, infants facing infection rely on maternal antibodies and a robust cytotoxic Th1 response. Enhanced cytotoxic function in infants fed breast milk may be promoted by bacterial ligands in breast milk.…”
Section: Proposed Function Of Microbiota In Human Breast Milkmentioning
confidence: 99%
“…In our study, the lowered levels of complement C4 in group 1 might be explained by Caetano's findings, 31 although lowered levels of C4 were also found in the control group. The importance of breast-feeding on native immunity was demonstrated by Tarcan et al 32 in a study comparing the percentage of NK cells between breast-fed and formula-fed infants; NK cell counts were significantly higher in breast-fed infants. 32 Similarly, Hawkes et al 33 demonstrated an increased CD8 lymphocyte count and decreased CD4/CD8 ratio in breast-fed infants.…”
Section: Discussionmentioning
confidence: 93%
“…The importance of breast-feeding on native immunity was demonstrated by Tarcan et al 32 in a study comparing the percentage of NK cells between breast-fed and formula-fed infants; NK cell counts were significantly higher in breast-fed infants. 32 Similarly, Hawkes et al 33 demonstrated an increased CD8 lymphocyte count and decreased CD4/CD8 ratio in breast-fed infants. In concordance with these studies, we demonstrated that different diets (milk TB Ozkan, E Sahin, G Erdemir et al Saccharomyces boulardii and paediatric diarrhoea formula or breast-feeding) might result in different immune profiles, confirming the synergism between breast milk and probiotics against infections and their combined effect on the consistency of intestinal flora during the early infantile period.…”
Section: -13mentioning
confidence: 93%
“…However, formulated milk does not seem to influence lymphocyte counts in the gut wall in piglets (Prims et al, 2016). In addition, only lower numbers of natural killer cells have been observed in peripheral blood of infants after formula feeding (Tarcan et al, 2004). This observation is important since maintenance of M cells in PPs relies on close interaction of the cell with B cells (Mach et al, 2005;Miyazawa et al, 2006).…”
Section: Discussionmentioning
confidence: 99%